The Function of the Minor Rustic Characters in Four of Thomas Hardy's Major Novels in relation to the theme of Marriage, Chastity, the Double Standard and Sexual Freedom - Segueira, Guiomar May (My University, 1968)
In this thesis, I attempt to examine the function of the minor rustic characters in four of the major novels of Thomas Hardy. The four novels are, Far from the Madding Crowd, The Mayor of Casterbridge, Tess of the d'Urbervilles and Jude the Obscure.
The purpose of this examination is to show to what extent the minor rustics help to reveal the theme of marriage, chastity, the double standard and sexual freedom. They do this either by furthering, or by not influencing, the plot; through the delineation of the characters of the protagonists; by their contribution to the humour, comic relief, and the chorus of the novels; and finally, by their rural values.
Keywords: English Language and Literature; English Language and Literature